2022
DOI: 10.1109/jestie.2021.3112929
|View full text |Cite
|
Sign up to set email alerts
|

Parameter Extraction Technique for Evaluation of Inductive and Capacitive Elements of Three-Winding Coupled Inductor

Abstract: Wide band gap devices have enabled miniaturization of the magnetic components to enhance the power density of the converter. However, parasitic components become dominant at higher switching frequencies that actuate unwanted electromagnetic interference issues. Therefore, it is critical to model and evaluate them in compact magnetic structures. Since multiwinding coupled inductive structures are essential part of multiphase converters, this paper introduces a measurement method to compute the parasitic element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In order to quantify the characteristics (or capacitive couplings) after the first resonant frequency/antiresonant frequency, the behavioural-based modelling method can be applied [46], which however, requires manufacturing prototypes first and then measuring the time-domain or frequency-domain response. Chokes and multi-phase inductors are more complex than single-phase inductors [49], [202], where more capacitive couplings should be taken into consideration due to the increased number of terminals.…”
Section: Magnetic Componentsmentioning
confidence: 99%
“…In order to quantify the characteristics (or capacitive couplings) after the first resonant frequency/antiresonant frequency, the behavioural-based modelling method can be applied [46], which however, requires manufacturing prototypes first and then measuring the time-domain or frequency-domain response. Chokes and multi-phase inductors are more complex than single-phase inductors [49], [202], where more capacitive couplings should be taken into consideration due to the increased number of terminals.…”
Section: Magnetic Componentsmentioning
confidence: 99%
“…Passive components are essential in power electronics converters [1], [2]. For the converters utilizing wide-bandgap devices [3], [4], the parasitic capacitance in magnetic components, including inductors [5], [6], transformers [7] and motors [8], is of significant importance due to the fast switching characteristics (high dv/dt value) of the wide-bandgap devices [8], [9]. It is reported that such parasitic capacitance can significantly contribute to the capacitive current during the switching transients [10] and may result in increased conducted noise and extra switching losses dissipated by the transistors [11]- [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, if the full fast switching capability of GaN switches were employed, EMI emissions would be drastically increased in comparison to the case of Sibased converters under similar operating conditions. Authors of [9] also concluded that by the use of WBG switches in cascaded boost converters, higher EMI is generated in a high frequency spectrum, and it is emphasized that for converters with WBG switching devices more attention needs to be paid to methods to reduce the ringing and parasitics in the circuit for EMI reduction [10].…”
Section: Introductionmentioning
confidence: 99%